PERBEDAAN SIKLUS MENSTRUASI ANTARA AKSEPTOR KB SUNTIK 1 BULAN DAN AKSEPTOR KB SUNTIK 3 BULAN DI BPM NY. “S” DESA KLUWIH KECAMATAN TULAKAN KABUPATEN PACITAN - Murniati Murniati; Astrilinda Cahya Putri (Jurnal Delima Harapan, 2019)
Menstruation is regular bleeding from the uterus as a sign that the uterus hasfulfilled its function. Based on preliminary data through interviews on long term acceptorKB 3 month injection and long term acceptor KB injection 1 month on 25 November 2016which amounted to 20 people in BPM Ny "S" of Kluwih village Tulakan sub district ofPacitan. Of the 10 people who injected 1 month injection is not complaining about themenstrual cycle. While from 10 injectors of 3 month injection, regular menstrual cycles were6 respondents (60%) and irregular menstrual cycle were 4 respondents (40%). This studyaims to determine the difference of menstrual cycle between 1 month injection acceptor and3 month injection acceptor in BPM Ny. S Village Kluwih Tulakan District Pacitan.This type of research is comparative analytic. The research design in this researchis analytical case control (retrospective). The variable in this research is menstrual cyclebetween 1 month injection acceptor and 3 month injection. Measuring tools used interview.Population of 80 injection contraceptive injectors (40 1 month injections of contraceptiveinjectors, 40 3 month injecting of KB acceptor) and 60 samples of KB acceptor usingaccidental sampling technique in February 2017.Method of data analysis using T test withsignificance determined by value ρ < 0.05.The results showed that the frequency of menstrual cycle of 1 month injections ofcontraceptive injectors showed that from 30 respondents, 26 respondents (86,7%),menstruation cycle 28-35 days (regular), and 3 month period of menstruation of 3 monthinjecting contraception showed that from 30 respondents obtained more than half or 21respondents (70%) menstrual cycle > 35 days (irregular). Based on the result of paired TTesttest, the signification level is 0,000 < 0,05 so that H0 is accepted, meaning that there isdifference of menstrual cycle of 1 month injection acceptor and 3 month injectioncontraceptive injection.It is suggested to the officer to increase the extension activity to KB injectors toincrease knowledge and insight about side effects of injecting KB.